PENERAPAN MEDIA POSTER DIGITAL DALAM PEMBELAJARAN PENULISAN PUISI UNTUK MENGEMBANGKAN KREATIVITAS SISWA KELAS X SMA NEGERI 2 MEDAN - Br. Nainggolan, Intan; Harahap, Rosmawaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing poetry is one of the productive language skills that requires students’ creativity in developing ideas, selecting appropriate diction, and expressing thoughts and feelings through aesthetic language. However, students still experience difficulties in finding ideas, developing imagination, choosing words, and producing creative poetry. This study aims to describe the implementation of digital poster media in poetry writing learning to develop the creativity of tenth-grade students at SMA Negeri 2 Medan. This research used a qualitative approach with a descriptive method. The data were collected through observation, interviews, and documentation. The subjects of this study were students of class X-8 at SMA Negeri 2 Medan. The results showed that the implementation of digital poster media provided visual stimuli that helped students develop ideas, imagination, diction, and poetry structures creatively. The use of digital poster media also created an interesting learning environment and encouraged students’ active participation during the learning process. Therefore, digital poster media can be used as an alternative learning medium to support students’ creativity in writing poetry.